Turn of mind - LaPlante, Alice, 1958- (Atlantic Monthly Press, 2011)
Implicated in the murder of her best friend, Jennifer White, a brilliant retired surgeon with dementia, struggles with fractured memories of their complex relationship and wonders if she actually committed the crime.